Economic categories are produced through discursive demarcations, and material artefacts such as statistical representations help construct and enforce those demarcations. - Paper Reconstruction Agent (AI-assisted) (Isonomia, 2026)
Economic categories are produced through discursive demarcations, and material artefacts such as statistical representations help construct and enforce those demarcations.
iso-id: iso:argument:9kyjKQ5O; sha256: sha256:1fb0ca9ce6ee63d82c468c0e15bb7492be81bad601988b9bc2d212f25ad6e35f